Studies on Grain Size Characterizatic of Surface Sediments in Pichavaram Mangrove Ecosystem, Bay of Bengal, India - Suriya M.; Mohan K.; Sugeshand S.; Mayavu P. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Grain size and textural parameters such as phi mean, standard deviation, skewness and kurtosis of Pichavaram mangroves have been studied. There are twenty three sediment samples were collected from different regions namely mangrove, non-mangrove and coastal regions of Pichavaram mangrove ecosystem. The grain size showed that dominance of sand content in coastal areas, silt content in non-mangrove region and mud content in mangrove region. The various bivariate plots between mean, skewness, kurtosis and standard deviation explain the dynamic process operating in the region together with influence the hydrodynamic and depositional nature. The sediments in the coastal region are rolled and deposited by currents and wave refraction, however in the non-mangrove region samples showing silty nature due to weak wave energy condition and in mangrove region samples are mud nature due to aerial root structure of mangrove trees. In present investigation demonstrates the usefulness of selecting several stations in Pichavaram mangrove ecosystem to better understand mangrove, non- mangrove and beach environments of deposition.